The Use of Phytochemicals to Improve the Efficacy of Immune Checkpoint Inhibitors: Opportunities and Challenges - Deniz Can Guven; Taha Koray Sahin; Alessandro Rizzo; Angela Dalia Ricci; Sercan Aksoy; Kazim Sahin (Applied Sciences, 2022)
Immune checkpoint inhibitors (ICIs) have revolutionized cancer therapy and reshaped medical oncology practice over the past decade. However, despite unprecedented and durable clinical responses, most patients eventually fail to respond to ICI therapy due to primary or acquired resistance. There is a great need for complementary alternative medicine, such as botanicals and nutritional supplements, because of their capability to modulate a myriad of molecular mechanisms to prevent immunotherapy resistance and reduce its adverse effects. Mounting evidence suggests that phytochemicals, biologically active compounds derived from plants, can favorably regulate key signaling pathways involved in tumor development and progression. In addition, phytochemicals have been found to exert anticancer effects by altering the expression of checkpoint inhibitors of the immune response. The immunomodulatory activity of phytochemicals in the tumor microenvironment has recently received immense interest. Based on these immunomodulatory activities, phytochemicals could be candidates for combination with ICIs in future clinical studies. The current review focuses on the available evidence for combining phytochemicals with a discussion on the promising opportunities to enhance the efficacy of immune checkpoint inhibitors and potential challenges resulting from these combinations.